Upaya Meningkatkan Hasil Belajar Peserta Didik Melalui Media Pembelajaran Wordwall pada Mata Pelajaran Bahasa Indonesia di Kelas V SD Negeri 060843 Medan Barat - Tambunan, Melinda; Zulfitri; Putri Juwita; Melvy Br Perangin-Angin (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to improve students' learning outcomes in Indonesian language subjects through the use of Wordwall interactive learning media. The background of the research is based on the low learning achievement of students in class V of SD Negeri 060843 West Medan, most of whom have not met the Minimum Completion Criteria (KKM). This research is a Classroom Action Research (PTK) with the Kurt Lewin cycle model which includes four stages: planning, action, observation, and reflection. The implementation was carried out in two cycles, with data collection through observation, documentation, and learning outcome tests. The results showed a significant increase in student learning outcomes. The average student score increased from 63.54 in the pre-cycle stage to 71.87 in cycle I and reached 83.12 in cycle II. The percentage of classical completeness also increased from 33% in the pre-cycle to 62.5% in cycle I and 87.5% in cycle II. This finding indicates that the use of Wordwall media not only improves students' understanding of the material, but also increases learning motivation and active involvement in the learning process. Thus, Wordwall media deserves to be used as an innovative alternative in teaching Indonesian language at the primary school level.